Hubungan Tingkat Kecemasan dengan Kualitas Tidur pada Mahasiswa yang Mengalami Dismenorea Primer - Rosa Lia Dina Carera; Arif Widodo (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Primary dysmenorrhea is a menstrual disorder that occurs in women and often has different effects on each individual. Psychologically, the pain it causes can trigger anxiety, preventing the body from having enough time to fall asleep. This study aims to investigate the relationship between anxiety levels and sleep quality in female students with primary dysmenorrhea. The method used is a quantitative approach with a true correlation design. The sample was drawn from a population of 144 female nursing students in the class of 2023 at Muhammadiyah University in Surakarta, with 106 respondents randomly selected. The analysis results show a significant relationship between anxiety levels and sleep quality in female students with primary dysmenorrhea, with a p-value of less than 0.01 and a correlation coefficient (r) of 0.560, indicating a moderate correlation. This means that the higher the anxiety of students with primary dysmenorrhea, the poorer their sleep quality tends to be. The conclusion of this study emphasizes the importance of a holistic approach to treating menstrual pain, focusing not only on pain management but also addressing anxiety. This is expected to improve sleep quality and overall well-being among students and serve as a basis for developing support and prevention programs campus.